Creation of nitrogen-vacancy centers in chemical vapor deposition diamond for sensing applications. (1st March 2022) - Luo, T; Lindner, L; Langer, J; Cimalla, V; Vidal, X; Hahl, F; Schreyvogel, C; Onoda, S; Ishii, S; Ohshima, T; Wang, D; Simpson, D A; et al.
Abstract: The nitrogen-vacancy (NV) center in diamond is a promising quantum system for magnetometry applications exhibiting optical readout of minute energy shifts in its spin sub-levels. Key material requirements for NV ensembles are a high NV − concentration, a long spin coherence time and a stable charge state. However, these are interdependent and can be difficult to optimize during diamond growth and subsequent NV creation. In this work, we systematically investigate the NV center formation and properties in bulk chemical vapor deposition (CVD) diamond. The nitrogen flow during growth is varied by over four orders of magnitude, resulting in a broad range of single substitutional nitrogen concentrations of 0.2–20 parts per million. For a fixed nitrogen concentration, we optimize electron-irradiation fluences with two different accelerated electron energies, and we study defect formation via optical characterizations. We discuss a general approach to determine the optimal irradiation conditions, for which an enhanced NV concentration and an optimum of NV charge states can both be satisfied. We achieve spin–spin coherence times T 2 ranging from 45.5 to 549 μ s for CVD diamonds containing 168 to 1 parts per billion NV − centers, respectively. This study shows a pathway to engineer properties of NV-doped CVD diamonds for improved sensitivity.